Effect of Dietary Sodium on α, β, and γ Epithelial Sodium Channel (ENaC) Gene Expression in Kidney Tubules of Wistar Rats - Ronny Lesmana; Genta Syaifrin Laudza; Trianing Tyas Kusuma; Hanna Goenawan; Yulia Sofiatin; Yuni Susanti Pratiwi; Nova Sylviana; Setiawan Setiawan (Majalah Kedokteran Bandung, 2019)
Hypertension is a condition of persistently high blood pressure. It is currently a big health issue as its prevalence is high in Indonesia and its complications are numerous and deadly. Salt intake is one of the modifiable factors of hypertension. According to a study by Indonesian Ministry of Health, salt consumption in Indonesia is almost two times greater than the recommended salt diet from WHO. Sodium reabsorption in kidney plays a role in regulating blood pressure. Epithelial sodium channel (ENaC) is one of the structures that function in sodium reabsorption in kidney tubules. This study was conducted at the Central Laboratory and Animal Laboratory of the Faculty of Medicine Universitas Padjadjaran from June to Desember 2018. The aim of this study was to analyze the effect of high sodium diet on the expression of ENaC gene in kidney tubules of rats. Twelve Rattus norvegicus wistar rats were divided into two groups of control and treatment. Treatment group was given daily 2 mL NaCl solution treatment using gavage for 8 weeks. The expression of ENaC α, β, and γ was obtained by running tissue samples from kidney cortex and medulla in polymerase chain reaction and electrophoresis. The result showed that there was an insignificant decrease in ENaC α, β, and γ gene expressions in both kidney cortex and medulla of the treatment group when compared to control groupThis study concludes that ENaC gene expression is not significantly affected by high sodium diet.Pengaruh Diet Tinggi Natrium terhadap Perubahan Ekspresi Gen Epithelial Sodium Channel (ENaC) pada Tubulus Ginjal TikusHipertensi merupakan kondisi tekanan darah tinggi dalam waktu lama. Prevalensi dan komplikasi hipertensi menyebabkan hipertensi menjadi isu kesehatan yang cukup besar. Jumlah asupan garam merupakan faktor hipertensi yang dapat dimodifikasi. Berdasar studi Kementrian Kesehatan Indonesia, konsumsi garam di Indonesia rerata dua kali lipat lebih banyak daripada rekomendasi WHO. Reabsorpsi natrium pada ginjal berperan penting pada regulasi tekanan darah. Fungsi ini diperankan oleh epithelial sodium channel (ENaC) yang berfungsi untuk reabsorpsi natrium. Penelitian ini dilakukan di Laboratorium Sentral dan Laboratorium Hewan Fakultas Kedokteran pada Juni–Desember 2018. Tujuan penelitian ini menganalisis efek diet tinggi natrium pada ekspresi gen dari ENaC di tubulus ginjal pada tikus. Duabelas ekor tikus Rattus norvegicus dibagi menjadi dua kelompok, yaitu kontrol dan perlakuan. Kelompok perlakuan diberikan 2 mL larutan NaCl setiap hari selama 8 minggu. Larutan diberikan melalui paksa (gavage). Ekspresi gen ENaC α, β, γ dari korteks dan medula ginjal diamplifikasi dengan PCR dan dideteksi dengan elektroforesis. Pita protein dari gel elektroforesis dinilai intensitasnya dengan software ImageJ. Hasil dari elektroforesis menunjukkan penurunan ekspresi gen ENaC α, β, γ di korteks dan medulla pada kelompok perlakuan dibanding dengan kontrol. Studi ini menyimpulkan ekspresi gen ENaC pada korteks dan medulla ginjal tidak signifikan dipengaruhi oleh diet tinggi natrium.